Efecto del tratamiento con anti-vegf sobre la agudeza visual en pacientes con maculopatía diabética - Quezada Palacios Richard Omar (2016)
The diabetic maculopathy is the pathophysiological consequence of VEGF action. The use of anti-VEGF (Bevacizumab) intravitreal has demonstrated efficacy and safety. Objectives: To determine the effect of treatment with anti-VEGF (Bevacizumab) intravitreal on visual acuity in patients with diabetic maculopathy. Method: A case-control study was conducted. The population are patients with diabetic maculopathy. Patients found improvement in visual acuity (logMAR delta greater than or equal to 0.3) and no improvement in visual acuity (delta less than 0.3 logMAR). Medical records were reviewed and cases (n = 50) who were treated with intravitreal injection of 1 or more doses of Bevacizumab and controls (n = 50), who they did not receive Bevacizumab (other treatments) were identified. Descriptive statistics, chi-square test of association and Z test for proportions was used. Results: 58 men and 42 women. An OR = 3.43 was found with 95% CI 1.4 to 7.9 (p = 0.003). In group cases, those with less than or equal to 15 years of diagnosis of diabetes mellitus improved compared to those with more than 15 years of diagnosis (p = 0.04). In case group, the number of doses: 24 patients (48%) used 1 dose; 16 patients (32%), 2 doses; 9 patients (18%), 3 doses and only 1 patient (2%), 4 doses. In group cases, it was found that those with less than or equal to 15 years of diagnosis required less than or equal to 2 doses compared to those with more than 15 years of diagnosis (p = 0.010). Conclusions: The effect of treatment with anti-VEG (Bevacizumab) is intravitreal association with improvement in visual acuity in patients with diabetic maculopathy. The time of diagnosis of diabetes mellitus influences the improvement of visual acuity only in the case group. The time of diagnosis of diabetes mellitus affects the number of doses of Bevacizumab in the case group. It was not possible to determine if visual acuity is significant in monitoring the anti-VEGF treatment parameter